Pengaruh Penggunaan Serbuk Kulit Cangkang Telur Sebagai Subsitusi Parsial Semen Terhadap Kuat Tekan Beton - Ashariyanto, Yudi; Diana, Anita Intan Nura; Deshariyanto, Dwi (Universitas Negeri Surabaya, 2022)
Concrete is a construction material that is the result of a combination of cement, coarse aggregate, fine aggregate, and water mixed together. The work of making concrete can be added an additional material for the benefit of construction work. In this study, 12 test objects (BU) were made using a mold in the form of a cylindrical diameter of 15 cm and a height of 30 cm. The tests carried out were in the form of testing the compressive strength of concrete at the age of 20 days, data analysis, simple linear regression analysis and hypothesis testing f, t test, significance test. The results showed that the variation of eggshell powder, the percentages of 0%, 5% and 10%, increased with an average value of the compressive strength of concrete by and while the variation of 20% experienced a decrease in the simple regression equation Y = 14210.600 + (- 2,957) from In the equation, the variable (X) is the higher the variation of eggshell powder, the (Y) will decrease the compressive strength obtained.